No gods and precious few heroes : Twentieth-century Scotland - Harvie, Christopher T. (Edinburgh University Press, 1998)
The fourth edition of this classic text on the history of Scotland since World War I. Epitomised by political, social and technological change this history appraises a fast-evolving century, from the outbreak of World War I up to the present and the politics of devolution and the age of the internet. The book begins with the devastating impact of World War I and Scotland's critical role in its conduct, then continues to explore Scots institutional life, from 1922 to 1964, governed by the problems of economy, society, politics and culture embedded in a mature industrialised state with economic problems and governmental deficits. Two further chapters cover the period from 1964 to 1999, including the challenge of new industries, oil discoveries, and the rise of devolutionary and nationalist politics. A new section for this edition covers the course of devolved politics, from the Scottish parliament of 1999 to the financial collapse of 2008 and the constitutional upheavals of 2014-15, rounding off this unique interpretation of a century of Scottish life from a cherished and multi-faceted historian.
Series numbering from series title page of v. 7.
Keywords: Scotland -- History -- 20th century.; Écosse -- Histoire -- 20e siècle.; HISTORY.; Scotland; 1900-1999; History